Evaluation of biofilm formation and chemical sensitivity of Salmonella typhimurium on plastic surface - Sani Aliyu, Nor Iza A. Rahman, Anas Muazu, Umar Faruk Abdullahi, Rochman Naim, Umma Muhammad, Mainul Haque (Journal of Applied Pharmaceutical Science, 2015)
S. typhimurium is an important socioeconomic problem in several countries, mainly in developing countries where it is reported as the main responsible for the food-borne disease outbreaks. A biofilm can be explained as a group of cells, diverse species or mono-species that are fixed to a surface and/or to one another. This study aimed to evaluate the biofilm formation of S. typhimurium on the plastic surface as well as to determine the relationship between contact time and incubation temperature. Crystal violet assay was performed to quantify the biofilm formation with and without treatments based on the value of optical density at 600nm of the destaining crystal violet at different interval of time. The outcomes of the result indicated that, the attachment of bacterial cells to the plastic surfaces increased with the increased contact time and determined by temperature. The values of OD600 at 37 °C for 24, 48 and 72 hours were 0.770, 0.968 and 2.363 respectively. This indicated that, the formation of biofilm by S. typhimurium on plastic surfaces varied with contact time. For the disinfectant treatments, hydrogen peroxide with 91 % sensitivity was the highest in treatment of S. typhimurium cells, followed by the mixture of sodium hypochloride and paracetic acid with 70 %, then paracetic acid with 67 %. Considering this result, S. typhimurium formed a biofilm on the plastic surface, hygienic activities on a plastic surface in food industry during handling, processing, distribution and storage of food should be a concerned and these disinfectants are suggested for the treatment of S. typhimurium.
Keywords: Biofilm. S. typhimurium, Plastic surface, Disinfectant, Treatment.